Analisis Efisiensi, Efektivitas, Dan Tingkat Kemandirian Penggunaan Dana Bantuan Operasional Kesehatan (BOK) Dalam Rangka Menilai Capaian Kinerja Program Di Puskesmas Gemaharjo Kabupaten Pacitan - Sulis Megawati; Arif Hartono; Ika Farida Ulfah (The Academy Of Management and Business, 2023)
Gemaharjo Health Center is one of the Community Health Centers with active Community Health Efforts (UKM) funded by Health Operational Assistance Fund (BOK). The purpose is to increase access to and quality of health services in the work area of the Gemaharjo Health Center. The purpose of this study was to analyze the efficiency, effectiveness, and level of independence in the use of BOK Funds in order to assess UKM at the Gemaharjo Health Center. The analytical method used is descriptive qualitative. The data used is the realization of BOK Fund and 2021 Gemaharjo Health Center Performance Assessment (PKP) data. The results of efficiency analysis are in the predictable category, as evidenced by the amalgamation of several unfunded activities, and can be seen from the increase in performance achievements from 2020 to 2021. Effectiveness analysis is included as an effective category, because of the success in managing BOK Fund to finance UKM. Evidenced by the increase in the achievements of Gemaharjo PKP from last year even though it had not yet reached the set target. Results of the analysis of the level of independence show that the use of BOK Funds at Gemaharjo Health Center is included in  the predictable category, that is, it has fulfilled most of the relevant targets.